2013
DOI: 10.1088/0253-6102/59/6/14
|View full text |Cite
|
Sign up to set email alerts
|

The Mathematical Analysis for Peristaltic Flow of Hyperbolic Tangent Fluid in a Curved Channel

Abstract: In the present paper, we have investigated the peristaltic flow of hyperbolic tangent fluid in a curved channel. The governing equations of hyperbolic tangent fluid model for curved channel are derived including the effects of curvature. The highly nonlinear partial differential equations are simplified by using the wave frame transformation, long wave length and low Reynolds number assumptions. The reduced nonlinear partial differential equation is solved analytically with the help of homotopy perturbation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Kumar et al (2017b) discussed an unsteady squeezed flow of a tangent hyperbolic fluid over a sensor surface in the presence of variable thermal conductivity. Nadeem and Maraj (2013) initiated the mathematical analysis for peristaltic flow of tangent hyperbolic fluid in a curved channel.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2017b) discussed an unsteady squeezed flow of a tangent hyperbolic fluid over a sensor surface in the presence of variable thermal conductivity. Nadeem and Maraj (2013) initiated the mathematical analysis for peristaltic flow of tangent hyperbolic fluid in a curved channel.…”
Section: Introductionmentioning
confidence: 99%
“…Where the constitutive equation for hyperbolic tangent fluid is given by Nadeem et al (2009Nadeem et al ( , 2013Nadeem et al ( , 2015 , …”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…However no work has done yet for blood flow in a curved artery (channel) with stenosis but some work has done for peristalsis. Nadeem et al (2013) discussed the peristaltic flow of the tangent hyperbolic fluid in a curved symmetric channel with sinusoidal waves.…”
Section: Introductionmentioning
confidence: 99%
“…Nadeem and Akram [12] addressed the peristaltic pumping of a hyperbolic tangent fluid through an asymmetric channel. Nadeem and Maraj [13] studied mathematically the peristaltic motion of a hyperbolic tangent fluid in a curved channel with the help of Homotopic perturbation method. Ali Abbas et al [14] reported the 3D peristaltic pumping of hyperbolic tangent fluid with flexible walls.…”
Section: Introductionmentioning
confidence: 99%